Caracterización de factores de riesgo cardiovascular en el personal administrativo de la universidad del Quindío (2015)
A descriptive study of 45 secretaries equaling 50% of the population that makes up the administrative staff of the University of Quindío was performed. In February 2015 to determine the cardiovascular risk factors in this population are, through the analysis of non-modifiable factors such as age, gender and cardiovascular history, modifiable factors which are the blood pressure, diet, exercise, snuff. Also the body mass index and waist ratio. Of those studied was detected that About 54% of the population are more likely Cardiovascular Risk, 4.47% have a family history of these diseases, 46.7% of the population presented a blood pressure between 111-139 and 11.1% had pressure above 140, 2.2% smoke 10 cigarettes a day, 40% have rich eating habits in sauces, fried foods, sweets, flour, etc., 31.1% people were found in overweight or obese at the time of collecting sample data. 22.2% with a BMI between 25 and 29.99, plus 4 are above 30 BMI, 55.6% of participants presented an index waist 71-80 cm and 3 above 100 cm , 17.8% quite clear risk of cardiovascular disease and 46.7% had a rare real risk and more than half of the participants did not exercising. In participants the main conditions are sedentary, BMI, poor eating habits, overweight. At the end of the document are some recommendations and strategies to work in cases of increased cardiovascular risk.